Quadriláteros Convexos Inscritos e Circunscritos - Portela, Claudinei Garcia (2021)
In this work we review conditions for a convex quadrilateral to be inscribed or circumscribed in a circle, that is, the theorems of Ptolemy and Pitot, in addition to some formulas about their areas given by Brahmagupta and Bretschneider. We also present conditions for the inscription of a circumscribed quadrilateral. A quadrilateral that can be both inscribed and circumscribed on some pair of circles is known bicentric quadrilateral. Finally, we highlight some properties of a kite quadrilateral and the conditions for a circumscribed quadrilateral to be a kite one. Keywords: Quadrilateral, Area, Bicentric Quadrilateral, Kite Quadrilateral.